EVALUATION OF NEWER FUNGICIDE FOR MANAGEMENT OF EARLY BLIGHT OF TOMATO IN CHHATTISGARH - D. K. SAHU; C. P. KHARE; H. K. SINGH; M. P. THAKUR (The Bioscan, 2013)
The present studies were conducted to test the efficacy of some newer molecules like pyraclostrobin, boscalid, and their combination maccani, pristine along with commonly used chemicals viz., mancozeb, copper oxychloride and chlorothalonil against early blight of tomato cultivar Pusa Ruby. A variant with no application of fungicide was used as a control. Average yield was calculated after fifteen pickings. Phytotoxicity effect of newer molecules was evaluated using a single spray. All fungicide treatments reduce the disease severity as compared to untreated check. Pristine 38%WG @ 64+126g a.i. /ha (31.88%) significantly reduced the disease followed by maccani 16%WG @ 60+180g a.i./ha (33.31%) and increase the yield from 33.50 tonnes/ha (Pristine 38%WG @ 64+126g a.i. /ha) and 32.44 tonnes/ha (maccani 16%WG @ 80+ 240g a.i./ha) as compared to a maximum disease (76.2%) and minimum yield of only 21.15 tonnes/ha in control. Overall results revealed that Pristine at both concentrations (64+126g a.i./ha and 76.8+151.2g a.i./ha) was found significantly effective in reducing the disease and increasing the fruit yield over control.